EU Citizenship Beyond Urban Centres Perceptions and Practices of Young People in East Central European Peripheral Areas - Lorenz, Astrid; Anders, Lisa H. (The Future of Europe, 2023)
This open access book provides in-depth and comparative analyses of how young people in peripheral areas in Poland, the Czech Republic, Slovakia, Hungary and Romania perceive EU citizenship. It also informs the reader about the challenges faced by EU Youth Dialogue projects that aim at promoting active (EU) citizenship in these areas and it offers context-specific recommendations for local, regional, national and European policymakers and people working with young people. The contributions are based on new qualitative data collected within the framework of the Jean Monnet Centre of Excellence at Leipzig University. It will be of interest to practitioners and scholars working on Europe and the EU, citizenship and the promotion of an active EU citizenship beyond urban centres.